Effects of Herbal Essential Oil Mixture as a Dietary Supplement on Egg Production in Quail - Metin Çabuk; Serdar Eratak; Ahmet Alçicek; Mehmet Bozkurt (The Scientific World Journal)
One hundred and eighty 7-week-old laying quail were fed various diets over a 12-week period. The diets included a control diet (without essential oil mixture (EOM) or antibiotics (ANTs)), a basal diet including EOM (24 mg/kg feed), and a basal diet including an ANT (avilamycin, 10 mg/kg feed). Each treatment comprised 4 replications with 4 cages (15 quail per cage), amounting to 60 quail per treatment group. Diets (in mash form) and water were provided for ad libitum consumption. EOM consisted of 6 different essential oils derived from the following herbs: oregano (Origanum sp.), laurel leaf (Laurus nobilis L.), sage leaf (Salvia triloba L.), myrtle leaf (Myrtus communis), fennel seeds (Foeniculum vulgare), and citrus peel (Citrus sp.). In comparison with the control diet, adding supplements such as EOM and ANTs to the basal diet increased egg production in quail (P<0.001). However, egg production was similar between EOM and ANT treatment groups. Moreover, there were no differences between the treatment groups with regard to egg weight. Feed intake was not affected by EOM or ANT supplementation, whereas feed conversion ratio was significantly improved by EOM and ANT supplementation. Thus, we concluded that EOM has beneficial effects as a dietary supplement on egg production and feed conversion ratio.